2022
DOI: 10.26504/rs145
|View full text |Cite
|
Sign up to set email alerts
|

Unequal Chances? Inequalities in Mortality in Ireland

Abstract: The mission of the Economic and Social Research Institute is to advance evidencebased policymaking that supports economic sustainability and social progress in Ireland. ESRI researchers apply the highest standards of academic excellence to challenges facing policymakers, focusing on 12 areas of critical importance to 21 st Century Ireland.The Institute was founded in 1960 by a group of senior civil servants led by Dr T.K. Whitaker, who identified the need for independent and in-depth research analysis to provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…Physical health risks of the COVID-19 virus were strongly related to age, with only 10 per cent of deaths among those under 65 (HPSC, 2023). Duffy et al (2022) show that deaths were somewhat less prevalent among those in professional/ managerial occupations, though effects are most marked for those under 65. Given illhealth is more prevalent among disadvantaged communities, it is possible that the effects of health resources being directed to fighting the pandemic, such as missed appointments, may have been disproportionately borne by disadvantaged individuals.…”
Section: Limitations Of the Study And Avenues For Future Researchmentioning
confidence: 90%
See 1 more Smart Citation
“…Physical health risks of the COVID-19 virus were strongly related to age, with only 10 per cent of deaths among those under 65 (HPSC, 2023). Duffy et al (2022) show that deaths were somewhat less prevalent among those in professional/ managerial occupations, though effects are most marked for those under 65. Given illhealth is more prevalent among disadvantaged communities, it is possible that the effects of health resources being directed to fighting the pandemic, such as missed appointments, may have been disproportionately borne by disadvantaged individuals.…”
Section: Limitations Of the Study And Avenues For Future Researchmentioning
confidence: 90%
“…Regarding mortality rates, Duffy et al (2022) found some evidence that some non-White and non-Irish-born/Irish nationals accounted for a higher share of COVID-19 deaths than their respective shares of the 65+ population. 29…”
Section: Disparities By Migration Statusmentioning
confidence: 99%
“…For example, in Ireland mothers who were born in Africa have a higher perinatal mortality rate compared to Irish-born mothers. ‘Black’, ‘Asian’ or ‘Eastern-European’ patients accounted for a higher proportion of COVID-19-related deaths in those over 65 years old in Ireland, and health disparities are stark for the minority Irish Traveller group [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%